The Groom Went Missing - Jenifer Ruff (Greyt Companion Press North Haven, CT, 2022)
"Second thoughts ... or something more sinister? Agent Victoria attends a lavish wedding as a guest of the best man. Everything is perfect and in place ... except the groom. Family and friends aren't sure if they should be angry or deeply concerned, until mounting evidence suggests the groom panicked and fled. But the bride and the best man don't believe it. They convince Victoria to find the missing groom and uncover the truth. Investigations reveal people's dirty secrets, and the guests at this wedding have many. But even Victoria doesn't anticipate the disturbing reality she unearths, and the life and death situations she'll face because of it."
Keywords: Detective and mystery -- Fiction; Investigations -- Fiction